A Method for the Inversion of Reservoir Effective Permeability Based on Time-Lapse Resistivity Logging Data and Its Application - Hairong Zhang; Bin Zhao; Shiqi Dong; Xixin Wang; Pengfei Jing (Geofluids)
Effective permeability is a key parameter for evaluating reservoirs and their productivity. With the wide application of resistivity logging tools in drilling, the advantages of resistivity logging in response to the dynamic invasion process of drilling fluids have become increasingly prominent. We analyzed the variation law of the measured resistivity data for different permeability formations at different times. In this study, we proposed an effective permeability modeling method based on the time-lapse resistivity logging data. First, based on the resistivity measurement data at different times, the dynamic resistivity profile of the reservoir was obtained through joint inversion; we then obtained the invasion depth and invasion zone resistivity of the drilling fluid at different times, along with the original formation resistivity. Subsequently, combined with parameters such as the soaking time, fluid viscosity, and saturation change of the drilling fluid, we obtained the phase permeability curve of the reservoir and dynamic effective permeability of the fluid near the wellbore. This study provides basic parameters for subsequent formation analyses and productivity prediction and substantially improves the reservoir evaluation technology from static to dynamic.